Maternal outcome of early versus late termination of pregnancy among pregnant mothers with prenatal diagnosis of lethal fetal anomalies: a retrospective review - Yong, SL; Abdulwahab, Dalia F; Ismail, Hamizah; Rozihan, I; Awang, Mokhtar; Abdullah, Suhaiza (Elsevier Ireland Ltd., 2012)
Objective: To compare the maternal morbidities between early (<22 weeks of gestation) and late (‡22 weeks of gestation) termination of pregnancy (TOP) among pregnant mothers with prenatal diagnosis of lethal fetal anomalies. Methods: This was a retrospective study reviewing all patients diagnosed prenatally to carry lethal fetal anomalies in Hospital Tengku Ampuan Afzan, Kuantan, Pahang, Malaysia during the year of 2011. Data was traced from patients’ medical record in hospital record office. These patients were divided into two groups, i.e. early and late TOP groups. The maternal morbidities and outcome of these two groups of patients were compared respectively. Results: There were 25 patients diagnosed to have lethal fetal anomalies, included fetuses with multiple structural abnormalities (40.0%), anencephaly or severe encephalocele (32.0%), nonimmune hydrops fetalis (16.0%) and syndromic fetuses (12.0%) i.e. Pentalogy of Cantrell and Edward’s syndrome. Seven (28.0%) and 18 (72.0%) patients had early and late TOP respectively. All patients with early TOP aborted vaginally. Among those with late TOP, five (27.8%) patients had complicated delivery, included three (16.7%) with assisted breech delivery and two (11.1%) with abdominal delivery. Patients with late TOP were more prevalent to morbidities compared to early TOP arm, i.e. frequent hospital admissions (33.3% vs. 14.3%), abnormal lie in labour (22.2% vs. 0.0%), symptomatic polyhydramnios requiring amnioreduction (22.2% vs. 0.0%), postpartum haemorrhage (16.7% vs. 0.0%), blood transfusion (11.1% vs. 0.0%) and uterine rupture (5.6% vs. 0.0%). Mean duration of hospital stay was slightly longer in the late TOP group (6.9 ± 4.1 days) than the early TOP group (5.7 ± 2.8 days). One patient with late TOP developed impending eclampsia requiring IV MgSO4 infusion. However, there was higher prevalence of retained placenta in the group of early TOP (28.6%) compared to the group of late TOP (5.6%). One patient with early TOP developed endometritis following manual removal of retained placenta. Conclusion: Patients with late TOP seem to have more morbidities compared to patients with early TOP though the sample size is too small to yield statistically significant result. It may suggest that early prenatal diagnosis and TOP are essential to minimise the maternal morbidities and improve the outcome. More data need to be recruited to prove this conclusion.